2016
DOI: 10.1513/annalsats.201604-294oc
|View full text |Cite
|
Sign up to set email alerts
|

Readiness for Implementation of Lung Cancer Screening: A National Survey of VA Pulmonologists

Abstract: Rationale: To mitigate the potential harms of screening, professional societies recommend that lung cancer screening be conducted in multidisciplinary programs with the capacity to provide comprehensive care, from screening through pulmonary nodule evaluation to treatment of screen-detected cancers. The degree to which this standard can be met at the national level is unknown.Objectives: To assess the readiness of clinical facilities in a national healthcare system for implementation of comprehensive lung canc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 42 publications
(53 reference statements)
1
11
0
Order By: Relevance
“…The percentage of lung cancers stage I/II and IV is similar to a previous study that demonstrated rates of 37% and 33%, respectively, prior to the implementation of lung cancer screening in a veteran population [25]. Infrastructure requirements for the establishment of a lung cancer screening program include the ability to characterize nodules with nonsurgical approaches, including bronchoscopic biopsy, and track outcomes of testing (complications and diagnosis) [26][27][28]. Thus, an onsite EBUS program facilitates the future establishment of a lung cancer screening program but may not necessarily expedite the time from detection to diagnosis.…”
Section: Discussionsupporting
confidence: 72%
“…The percentage of lung cancers stage I/II and IV is similar to a previous study that demonstrated rates of 37% and 33%, respectively, prior to the implementation of lung cancer screening in a veteran population [25]. Infrastructure requirements for the establishment of a lung cancer screening program include the ability to characterize nodules with nonsurgical approaches, including bronchoscopic biopsy, and track outcomes of testing (complications and diagnosis) [26][27][28]. Thus, an onsite EBUS program facilitates the future establishment of a lung cancer screening program but may not necessarily expedite the time from detection to diagnosis.…”
Section: Discussionsupporting
confidence: 72%
“…30,31 We used data from a national VHA survey conducted in 2013 to 2014 to determine whether facilities had capacity to perform thoracic surgery. 32…”
Section: Jama Network Open | Oncologymentioning
confidence: 99%
“…By contrast, surveys indicate that systems and processes of care to facilitate nodule evaluation have not been consistently adopted in US medical facilities. 119,120 Studies that include more diverse practice settings have reported higher and more variable rates of biopsy and complications. 88 8.…”
mentioning
confidence: 99%